GAMBARAN PENGETAHUAN IBU HAMIL TENTANG STUNTING DI DESA CIBENTAR KECAMATAN JATIWANGI KABUPATEN MAJALENGKA - Ai Fitri Irwanti; Euis Lelly Rehkliana; Sumarni (Jurnal Kesehatan Mahardika, 2020)
Stunting can occur at pre-conception. When a teenager becomes a mother with poor nutritional status, it can affect the occurrence of stunting. This condition gets worse when the nutritional intake is insufficient during the pregnancy period. The purpose of this study was to determine the description of knowledge pregnant women about stunting in Cibentar Village, Jatiwangi District, Majalengka Regency in 2020. The type or research design used is descriptive method. In this study, researchers used a total sampling technique with a total sample of 45. The instrument used was a questionnaire tailored to the purpose of the study. The results of this study indicate that the Description of Knowledge Pregnant Women about Stunting in Cibentar Village, Jatiwangi District, Majalengka Regency 16% Knowledge a good category of 7 people, then 24% with enough categories and 60% with less. It is recommended that with this study health workers in the village provide input, information and information related to stunting to increase the knowledge of teenagers, women of childbearing age, pregnant women and breastfeeding mothers in an effort to prevent stunting.